Pengaruh Work Family Conflict dan Kualitas Kehidupan Kerja Terhadap Stress Kerja Dan Kinerja Perawat Pada Rumah Sakit Umum Sidikalang Kabupaten Dairi - Adrian, Yudi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine the effect of Work Family Conflict on Nurse Performance at Sidikalang Public Hospital in Dairi Regency. To find out the effect of Quality of Work Life on Nurse Performance .To determine the effect of Work Family Conflict on Nurse Performance through work stress. To determine the effect of Quality of Work Life on Nurse Performance through Work Stress at Sidikalang Public Hospital in Dairi Regency. To find out the effect of Work Stress on Nurse Performance at Sidikalang District General Hospital. totaled 134 people. The method of determining the number of samples is done by census, which makes all members of the population become samples so that the number of samples that will be the object of research by the author is 134 people. Based on the results of research and discussions that have been conducted, several conclusions can be drawn, namely Work family conflict has a negative and significant effect on the performance of nurses in Sidikalang Regional General Hospital. The quality of work life has a positive and significant effect on the performance of nurses in Sidikalang Regional General Hospital. Work family conflict has a negative and significant effect on nurses 'performance through nurses' work stress at Sidikalang Regional General Hospital Quality of work life has a positive and significant effect on nurses 'performance through nurses' work stress at Sidikalang Regional General Hospital. Job stress, a negative and significant effect on the performance of nurses at Sidikalang Regional General Hospital.